Measuring and Analyzing the Impact of Macroeconomic Variables on Agricultural Exports in Egypt for The Period 1990-2022 - Rihal Qasim; Iman Rashad (تنمیة الرافدین)
This study aims to examine the impact of some macroeconomic variables on Egyptian agricultural exports, which are characterized by their low relative importance in total export values. The research problem is that Egypt's agrarian exports suffer from several structural imbalances. The study relied on two approaches: the first is descriptive and relies on theoretical research, and the second is quantitative and relies on standard economic methods and techniques. To achieve the study objective, a standard model was adopted that included several variables, including agricultural output values, foreign direct investment, exchange rate, inflation rate, and agricultural support as independent variables. In contrast, the values ​​of agricultural exports were adopted as a dependent variable during the period 1990-2022, based on the hypothesis that several macroeconomic variables play different roles in the values ​​of agricultural exports in Egypt. The study reached several conclusions, the most important of which is that most macroeconomic variables contributed to enhancing agricultural exports in the short and long term. It also made several recommendations, the most important of which is adopting agricultural policies that work to achieve economic efficiency and competitiveness in Egyptian agriculture, especially in the field of producing crops designated for export, because this type of policy leads to increased interdependence between countries, especially in the aspect related to exports, and in a more effective manner.